Kelayakan Media Pembelajara E-learning Berbasis Edmodo Untuk Mata Pelajaran Keamanan Pangan - Silfia Mifthahul Jannah; Desy Tri Inayah (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2022)
The purpose of this study was to determine the feasibilitiy of edmodo based e-learning media for food safety subjects for class X Muhammadiyah Vocational High School 4 Yogyakarta. This research method is research and development (R&D), with the ADDIE development model consisting of analyze, design, development, implementation, evaluation. The results showed that the average value of 2 observers on the small-scale test was 30.00 with percentage of 100% which means “worthy”, and on the large-scale test the average value of 30.00 with a percentage of 100% which means “worthy. Based on the results of the average value of two, it can be concluded that the feasibility of the edmodo based e-learning media is “appropriate” to be used as a learning medium for food safety subjects. Keywords: e-learning, edmodo, food safety